Assessment of fire safety preparedness among residential staff of the University of Ibadan: promoting safety in homes for national development (2017)
Fires in schools are a public concern because of the increased incidences, injuries and deaths of students and staff not to mention the destruction of properties. Despite this, schools seem not well prepared for fire disasters, The purpose of this study was to assess fire safety preparedness among residential staff in University of Ibadan. The research adopted a descriptive survey. The target population for this study consisted of all staff residing in the staff quarters. This study employed multistage sampling technique to obtain the sample population of 169 respondents. Data was collected by means of questionnaire, an observation schedule and structured interview guide. Data collected was analyzed through descriptive statistics and linear regression analysis. Based on the findings of the study, fire extinguishers are indicated not readily available in staff residential quarters with only 14.2% of residential staff indicating its availability; 57.4% of residential staff do not know how to use a fire fighting equipment; 85.2% of residential staff have not received any training on the use of fire fighting equipment. Based on the findings of the study, the researchers recommended that the university management should consider providing fire fighting equipment to staff residential quarters and should also be regularly inspected. Finally, residential staff should be trained on fire safety. The study suggested that a similar study should be carried out in other tertiary institutions in Nigeria to examine fire safety preparedness in schools, hence improve research and innovation in health and safety education for national development